Editorial Anti-VEGF Therapy: Proactive or Reactive? - Mahmood, Sajjad (Pakistan Journal of Ophthalmology, 2018)
One of the greatest breakthroughs in ophthalmology occurred only ten years ago following the first publication of the use of intravitreal bevacizumab to treat choroidal neovascularisation.1 Since then the use of anti-VEGF agents bevacizumab, ranibizumab and aflibercept has spread on a massive scale throughout the world and patients are benefiting from sight-saving therapy for diseases which previously had limited or no effective therapy.